THE ISLAMIC EXTENSION STRATEGY FOR MUSLIM CONVERTS IN REMOTE CULTURAL SOCIETIES: A CASE STUDY OF THE MERATUS DAYAK TRIBE - Arafat, Gusti Yasser; Budi Guntoro; Roso Witjaksono (UIN Antasari Banjarmasin, 2024)
The key determinants in the extension of Islamic values and practices to a particular rural community lies in the specific meticulous strategies in order to result in the expected outcome. This study qualitatively elaborates scrupulous decent strategies in the extension of Islam to the Dayak tribe on Meratus mountain. The strategies proposed are formulated from to field observation where the researcher participated directly in the act of the community and conducted deep interviews with the indigenous people. The data are analyzed using Miles and Hubberman's cyclic data analysis. The validity and credibility of the data are checked through external validity and triangulation of data sources and methods. The effectiveness of extension and communication strategies are discussed through the viewpoint of extension and communication studies. The preaching of Islam to the community relies on religious axioms that are discussed through the viewpoint of religious studies. Meanwhile, an ethnographic approach is used to understand the life of the Meratus Dayak tribe as the target of the extension. The results of this study is expected to reveal opportunities in extending Islamic values into the life of Meratus Dayak tribe as it shows the traditional values of their heritage. Appreciations and harmonious relationship to their culture and tradition determines the success of Islamic religious extension to their community.